(3fgGjI GdhUhd aj OQGjI GdCUhds - (3Uai GdOjf CHh YHO Gddg CMeO Hf YHO GdQMje GdCQehis; (3eMeO Hf YeQ Hf GdMSf Hf GdMSjf GdJjej GdHcQj, CHh YHO Gddg, aNQ GdOjf GdQGRqj,J (B606 (3g` s
(3BNQgG (B:s
(3GdeSCdI GdKGdKI ai Cf fSN CUd GdbjGS gd gh fSN ddaQY Ce dG s
(3GdfSNI HgG MhGTs
(3bdjd GdEYLGes
(3fSNI KGdKIs
(3bQf GdfSN (B:s
(3GdbQf GdSGHYs
(3GdJhKjbGJ GdeQLYjI (B:s
Keywords: (3CUhd Gdabgs